Extracorporeal lung support in patients with spinal cord injury: Single center experience. (4th March 2017) - Lotzien, Sebastian; Schildhauer, Thomas A.; Aach, Mirko; Strauch, Justus; Swol, Justyna
Abstract : Objective : Trauma-related spinal cord injury (SCI) leads to a loss of motor, sensory and vegetative functions and is disproportionately associated with respiratory complications. SCI has a significant impact on respiratory muscle function and can lead to respiratory dysfunction or severe lung failure. Participants : Between 2008 and 2014, 7 patients with severe lung failure following SCI received veno-venous extracorporeal membrane oxygenation (ECMO) n = 5 and interventional lung assist (iLA) n = 2. Results : The median duration of extracorporeal lung support was 8 (5.7–17.6) days. All 5 of the ECMO-supported patients were successfully weaned, and one of the two patients treated with iLA was weaned from the device. The median intensive care unit (ICU) stay was 35 (8.5–44.5) days. The mean hospital stay was 81 (8.5–120.7) days, and the average ventilation time was 817 (206–1, 225) hours. Five (71.4%) of the 7 patients were discharged from the ICU and hospital. Conclusions : In patients with SCI, serious complications include microatelectasis, infection, ventilation-perfusion mismatching and aspiration (special case: salt-water aspiration after jumping into shallow water). In patients with SCI with post-traumatic lung failure, ECMO is a feasible and life-saving procedure. After surviving spinal shock, a long rehabilitation period with intensive follow-up in specialized centers is required.